1996
DOI: 10.1016/0921-4534(96)00230-4
|View full text |Cite
|
Sign up to set email alerts
|

Vortex response and critical fields observed via RF penetration depth measurements on the superconductor YNi2B2C

Abstract: Measurements of the rf penetration depth λ(T, H, θ) are used to study the superconducting order parameter, vortex dynamics in the mixed state and delineate critical fields in the borocarbide superconductor YNi2B2C. The lower critical field has an anomalous T dependence, Hc1(T ) = 1.12 [1 − (T /Tc)] kOe, which is however consistent with independent superfluid density measurements at microwave frequencies. The vortex response is dominated by viscous flux flow, indicative of extremely weak pinning, and is paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…From the magnetization measurements for YNi 2 B 2 C, both the PE at high B and the second-magnetization-peak at lower B have been observed [15,16]. As far as we know, however, transport measurements to explore dynamic as well as static vortex properties have not yet been conducted except for quite limited cases [17,18]. Another interesting issue is that this material shows a variety of vortex-lattice structures, such as square and triangular lattices, in the B-T plane, which were revealed by small angle neutron scattering [19,20] and STM/STS [21].…”
Section: Introductionmentioning
confidence: 97%
“…From the magnetization measurements for YNi 2 B 2 C, both the PE at high B and the second-magnetization-peak at lower B have been observed [15,16]. As far as we know, however, transport measurements to explore dynamic as well as static vortex properties have not yet been conducted except for quite limited cases [17,18]. Another interesting issue is that this material shows a variety of vortex-lattice structures, such as square and triangular lattices, in the B-T plane, which were revealed by small angle neutron scattering [19,20] and STM/STS [21].…”
Section: Introductionmentioning
confidence: 97%
“…In the vortex state, Z s is determined by the vortex dynamics. Since the present microwave frequency is three orders of magnitude higher than the vortex pinning frequency of YNi 2 B 2 C [22], a completely free flux flow state is realized. In the flux flow state, two characteristic length scales, namely λ L and the flux flow skin depth δ f ∼ 2ρ f /µ 0 ω, appear in accordance with the microwave field penetration.…”
mentioning
confidence: 99%
“…The oscillator is ultra-stable, (approximately 1 Hz in 4 MHz), and this leads to very high sensitivity, with typical resolutions of a fewÅ. Earlier experiments in cuprate superconductors have led to a wide variety of information regarding superconducting parameters such as the lower critical field H c1 and pinning forces κ P [12] and have also been recently used to study borocarbide superconductors where they have revealed new features in the H-T phase diagram [13,14]. The primary advantage of our technique is the ability to probe both the resistivity in the normal state and superfluid density in the superconducting state which is not possible with conventional techniques such as DC resistivity or AC susceptibility.…”
Section: A Rf Setupmentioning
confidence: 99%
“…Magnetic fields upto 70 kOe were applied using a superconducting magnet. This experimental technique has been extensively used to study high and low T c superconductors both in the Meissner and mixed states [12][13][14]. If either the skin depth δ or the superconducting penetration depth λ changes as functions of T or H, these changes can be measured as changes ∆f in resonant frequency using ∆(δ or λ) = −G ∆f , where G is a geometric factor.…”
Section: A Rf Setupmentioning
confidence: 99%